Collecting meaningful data on labour use in onfarm trials in subSaharan Africa - Spencer, D. (Cambridge University Press, 1993)
In order to measure the effects of new agricultural technologies on labour productivity in sub-Saharan Africa, on-farm trials are usually conducted using small plots. Farmers who keep no records have to be interviewed frequently to minimize the effect of memory loss on the accuracy of the data collected. In this paper, results are reported of experiments in the forest zone of Nigeria and the semi-arid Sahel of Niger. They show that if researchers can take steps to fix events in the memory of farmers, accurate labour use data can be collected in interviews as long as three months after the events being recalled. A range of plot sizes, with a minimum of 350 m2 in the forest zone, needs to be used to measure accurately labour use per hectare and to take into account the effect of economies of size on crop production.